VITAMIN D3 IN TREATMENT OF OSTEOPENIC SYNDROME IN CHILDREN WITH GROWTH DISORDERS - Shcherbatiuk, N. Yu. (International Journal of Medicine and Medical Research, 2022)
Background. The efficacy of vitamin D3 agents for impaired growth of children of different cause was studied in the research. A positive effect on bone mineralization and calcium-phosphorus metabolism was evidenced. The treatment and prophylaxis charts using this drug for osteopenic syndrome are developed for children with hypothalamic-pituitary dwarfism, subdwarfism and dwarfism of constitutional genesis. Objective. The aim of the research is to study the effect of calcimine and vitamin D3 in cases of impaired bone mineral density in children aged 6-18 years old with growth retardation of the hypothalamic-pituitary genesis, subdwarfism and dwarfism of constitutional origin. Methods. The study involved 25 children, aged 6-18 years old with growth retardation: hypothalamic-pituitary (10 children), subdwarfism (5 children) and dwarfism of constitutional origin (10 children). The control group consisted of 20 children. The structural and functional state of bone tissue was studied using a two-photon X-ray densitometer “Lunar”. In the study of calcium-phosphorus homeostasis, the level of calcium and the level of phosphorus in the blood serum were determined. Serum alkaline phosphatase levels were also studied as a marker for bone formation. Results. In the examined children, there was a significant calcium deficiency at the level of the vertebrae L1–L4. The calcium content in L1 was 72.8%, L2 – 75.7%, L3 – 81.2%, L4 – 80.1%, which significantly differed from bone density in healthy children of a similar age and body weight. It was also revealed that in children diagnosed with growth retardation of the pituitary genesis, bone rarefaction was diagnosed in 100% of cases, while with subdwarfism and dwarfism of constitutional genesis these indicators were 43% and 24%, respectively. Conclusions. A differentiated choice of vitamin D3 treatment, depending on the degree of osteopenia in children, allows adjusting the calcium metabolism and preventing osteoporosis in children with stunted growth. Vitamin D3 in the complex treatment of osteoporosis in children with growth impairment of different genesis normalizes calcium-phosphorus homeostasis, which increases bone mineral density and, therefore, reduces osteoporotic changes by stopping leaching of calcium from bones.